Effect of papaya ringspot virus on growth, yield and quality of papaya (Carica papaya) cultivars - A THIRUGNANAVEL; T N BALAMOHAN; G KARUNAKARAN; S K MANORANJITHAM (The Indian Journal of Agricultural Sciences, 2015)
The field experiment was conducted during 2008 – 2010 to study the effect of papaya ringspot virus – type P on growth, yield, and quality of papaya (Carica papaya L.) varieties under PRSV infected conditions at Tamil Nadu Agricultural University, Coimbatore. Significant variation was observed for disease score, DAS-ELISA, tree growth, fruit parameters, yield, and quality characters among the varieties evaluated. The results revealed that all the papaya varieties tested were ELISA positive and PRSV adversely affected the growth, yield and quality of papaya varieties. Among the cultivars evaluated, CP 50 performed better even under PRSV infected conditions and recorded the lowest disease score (1.9), ELISA value (0.198), highest plant height (255.60 cm), stem girth (41.76 cm), number of leaves (41.78), maximum yield (29.26 fruits/plant), dry papain production (8.3 g dry papain/fruit) and tyrosine unit (139.2).